The Influence of Interpersonal Communication on the Prevention Action of Dengue Hemorrhagic Fever (DHF) in Meo-Meo Public Health Center of Baubau City - Budi Utama1 , Andi Zulkifli2 , Hasnawati Amqam3 , Wahiduddin2 , A. Arsunan Arsin2 , Lalu Muhammad Sa (Institute of Medico-legal Publications Pvt Ltd, 2021)
Dengue infection is a global health problem. One of the city in Indonesia that has a high incident of DHFis Baubau City, especially the area of Meo-Meo Public Health Center in 2016 to 2018 ranked first of theincident of DHF respectively for three years among 10 Public Health Center on the coastal area and thirdamong 17 Public Health Center in Baubau City. DHF cases are not only caused by mosquitoes, but alsoby human behavior that does not carry out healthy and indifferent lifestyles in the environment wheremosquitoes nest. Such behavior includes leaving the hanging used clothes, does not drain the tub, leavingpuddle around the residence. This study involved 39 people in the intervention group and also in the controlgroup who met the criteria including the age of 17-65 years old, can read, write, and communicate well,and willing to participate in this study. The result indicates a significant from the intervention groups to thecontrol group (p< 0.05), is action (p=0.001), and the difference in the percentage of action in both groups.So, it can concluded that interpersonal communication is more influential than counseling on increasingDHF prevention action.